Predictors of Outstanding Performance of Basic Education Teachers - Bonimar Tominez; Leila Dela Cruz (Philippine Association of Institutions for Research, Inc., 2015)
Basic education teachers play a vital role in the attainment of quality education in the country; they build the educational foundation of young minds. This study determined the teaching performance of basic education teachers in the Division of Nueva Vizcaya using the NCBTS framework as an evaluation tool. The descriptive-inferential design was employed in this study. Data were statistically analyzed through frequency counts, means, t-test, f-test, post hoc test, correlation procedures and multiple regressions. Teachers with family responsibilities manifest a higher teaching performance in dealing with diverse learners, the community and their own personal and professional advancements. Teachers with higher teaching position demonstrate a higher teaching performance in providing a safe learning environment, addressing individual differences, communicating learning goals, and evaluating learning outcomes. Teachers with higher salary grade reflect a higher teaching performance by serving as a role model to their pupils, establishing standards of learner's behavior, designing instructional activities for diverse learners to attain high standards of learning, and maximizing learning through appropriate evaluation procedures. The remarkable teaching performance of teachers in domains of social regard for learning, learning environment, diversity of learners, curriculum, and planning, assessing and reporting was strongly predicted by their high salary grade. Teachers ' gender predicted their excellent performance in dealing with the multiplicity of learners.